Muscle wasting in young patients with dilated cardiomyopathy. Issue 4 (1st March 2017) - Hajahmadi, Marjan; Shemshadi, Sara; Khalilipur, Ehsan; Amin, Ahmad; Taghavi, Sepideh; Maleki, Majid; Malek, Hadi; Naderi, Nasim
Abstract: Background: Muscle wasting can be accelerated by chronic diseases such as heart failure and is one of the major causes of disability, morbidity, and mortality in this population. We aimed to investigate the incidence of muscle wasting and its associated factors in dilated cardiomyopathy patients younger than 55 years of age. Methods: Between April 2014 and December 2015, all symptomatic patients with a diagnosis of non‐ischaemic dilated cardiomyopathy who were referred to heart failure clinic were included in our study. Dual energy X‐ray absorptiometry was used to evaluate body composition and identify muscle wasting. Muscle mass was calculated as the ratio of an individual's total lean mass of legs and arms (also called appendicular skeletal muscle) to their squared height (kg/m 2 ). The muscle mass values of less than 5.45 kg/m 2 for women and 7.26 kg/m 2 for men were considered low. Results: A total of 55 patients (32 male) were included. The mean (standard deviation) of age was 37.3 (10.1) years, and the mean of left ventricular ejection fraction was 21.4%. Most of the patients were in the New York Heart Association classes of II and II–III. Twenty‐six patients (47.3%) met criteria for muscle wasting. Patients with muscle wasting had lower left ventricular ejection fraction, lower 6‐min walk distance, and higher New York Heart Association function class and hospitalization rate. Conclusions: We concluded that muscle wasting might be present in younger patients with heart failure, particularly in those who are in worse clinical condition.